AUTO-SCALING DISTRIBUTED ETL SYSTEMS WITH SERVERLESS PLATFORMS - Santoshkumar Anchoori (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This comprehensive article explores the evolution and implementation of auto-scaling distributed ETL systems using serverless platforms. The article examines how serverless architectures revolutionize traditional ETL processes by providing dynamic resource management, improved scalability, and cost-effective operations. The article investigates performance optimization, memory management, concurrency handling, and security considerations in serverless ETL implementations. The article demonstrates how serverless platforms address traditional ETL challenges through detailed analysis of real-world deployments while offering enhanced reliability, reduced operational overhead, and improved resource utilization. The article also explores technical challenges and mitigation strategies, providing insights into best practices for implementing serverless ETL solutions in modern data processing environments.